Cutaneous Oxalosis Due to Primary Hyperoxaluria. (December 2022) - Ly, Sophia; Rick, Jonathan; Goff, Rachel; David, Bre Ana; Kincannon, Jay; Shalin, Sara
Abstract: A 19-year-old girl presented to the emergency department with a progressively painful purpuric lesion on the left dorsal foot, which had initially appeared 2 days prior. Three months earlier, she had been diagnosed with end-stage renal disease. Her medical history also included recurrent urolithiasis for the past 5 years and liver failure. Biopsy revealed oxalate crystals occluding vessels with secondary epidermal and dermal ischemia. Oxalate crystals were also visualized in the vessel walls and free in the subcutis. Genetic testing confirmed the diagnosis of primary hyperoxaluria type 1. She was treated with sodium thiosulfate, apixaban, pentoxifylline, wound care, and palliative care. At 4-month follow-up, the cutaneous manifestations of oxalosis were confined to only her feet, and she was undergoing evaluation for combined liver and kidney transplant. Cutaneous oxalosis because of primary hyperoxaluria should be considered in young patients presenting with purpuric lesions, recurrent urolithiasis, and early-onset renal failure.